Alvin and the Chipmunks : the junior novel - Finn, Perdita; Vitti, Jon.; McRobb, Will.; Viscardi, Chris; Bagdasarian, Ross. (New York : HarperEntertainment, 2007)
Alvin, Simon, and Theodore may have a cozy life in the woods, but when their tree gets chopped down, they are suddenly transported to the big city--and rock stardom!
"Based upon the characters Alvin and the Chipmunks created by Ross Bagdasarian"--T.p.
Keywords: Chipmunks (Musical group) -- Juvenile fiction; Chipmunks -- Juvenile fiction